INSPIRAÇÃO NORDESTINA: UMA LEITURA TEOLÓGICA NA POÉTICA DE PATATIVA DO ASSARÉ NA POENTE DO DIÁLOGO ENTRE TEOLOGIA E LITERATURA - NUNES, OZEAS DA SILVA (2008)
This thesis analyses the poetry of a famous writer from Ceara, Antonio Gonçalves da Silva, best known as Patativa do Assaré. This research is based on a literary criticism, specifically of those texts elaborated by Antonio Cândido that deal with issues related to history and society, and on a discussion about the establishment of a dialogue between theology and literature. The perspective of Eli Brandão points out the need of rewriting a literary text taking as reference sacred texts, will be useful for the achievement of this very purpose. With these two approaches, Cândido’s and Brandão’s, this investigation aims to find out its plausibility through out the dialogue between theology and literature. In other words, in Assare’s writings it is possible to perceive existential questions regarding the everyday problems in the lives of those who live in the sertão. The aspects highlighted in his poems lead to several theological questions and themes revealing, not only the hard reality of the northeastern Brazilian people, but also their faith, hopes and beliefs. The God presented by Pataiva do Assaré is not a God that repays you for the bad things you have done to others, but a God that sees the sufferings, exclusions and illnesses of those who are abandoned in the sertão. Therefore, we believe that the proposal to study Assare’s poetry from a theological point of view could be a good way to bring out those “northeastern theological themes” that came out as a result of the contact between the poet and Catholicism; topics that according to Assare’s thought bring out new meanings and interpretations.